How Transparency Kills Information Aggregation (And Why That May Be A Good Thing) - Sebastian Fehrler; Niall Hughes (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We show theoretical and experimental results that demonstrate the potential of transparency to influence committee decision making and deliberation. We present a model in which committee members have career concerns and unanimity is needed to change the status quo. We study three scenarios - secrecy, where votes and communication are secret, mild transparency, where individual votes are public, and full transparency, where both communication and individual votes are public. The two transparency regimes affect deliberation in different ways but lead both to a breakdown of information aggregation. However, transparency lowers the probability of an error if maintaining the status quo is the correct choice. As a consequence, the principal is better off in expectation under transparency than under secrecy if the cost of wrongly changing the status quo is high enough. We test the model's key predictions in a laboratory experiment varying the level of transparency between treatments. We observe strong effects of transparency on committee error rates that are largely consistent with the model. On the individual level, we observe strong effects on deliberative behavior which go in the predicted direction but are less pronounced than in theory.
Keywords: C92; D71; D72; 330